Study the Effect of The Announcement Traffic Indication Messages Window ATIM Size on the Performance of the Ad-hoc Networks in Power Saving Mode PSM - Mohammed Hijazieh; Mais Sultanah (Tishreen University, 2020)
The researches were interested in power saving in IEEE 802.11 standard in both of infrastructure networks and ad-hoc networks, where the power saving is one of the critical issues affecting wireless local area networks WLANs performance, especially ad-hoc networks, because each mobile device operates on the power of its limited battery. In ad-hoc networks which are called the independent basic service set IBSS  the power is saved by power saving mode PSM algorithm which depends on dividing the time into a number of  Beacon  intervals BIs, these intervals begin with a small period called announcement traffic indication messages window  ATIM period during which all the nodes are in the active mode. In this article, we study the effect of the announcement traffic indication messages window ATIM size on the performance of the  wireless networks in terms of power consumption and  throughput of the wireless network through several scenarios in the power saving mode PSM that differs in terms of the number of nodes used in the wireless network and the size of ATIM window. اهتم الباحثون بموضوع توفير الطاقة في معيار IEEE 802.11  في كل من الشبكات ذات البنية التحتيةInfrastructure  وشبكات Ad-hoc حيث يعد موضوع توفير الطاقة من القضايا الحرجة والمؤثرة على أداء الشبكات المحلية  اللاسلكية WLANs وخصوصا في شبكات Ad-hoc وذلك لأن كل جهاز جوال يعمل بالاعتماد على طاقة بطاريته المحدودة. يتم توفير الطاقة في شبكات Ad-hoc والتي تسمى مجموعة الخدمة الأساسية المستقلة IBSS باستخدام خوارزمية وضع توفير الطاقة PSM التي تعتمد على تقسيم الزمن إلى عدد من الفواصل الزمنية لإطار المرشد اللاسلكيBIs وتبدأ هذه الفواصل بفترة زمنية صغيرة للإعلان عن أطر التحكم تسمى بفترة نافذة رسائل إعلان إشارات المرور ATIM  تكون خلالها كافة العقد في وضع النشاط. تم في هذه المقالة دراسة تأثير اختلاف حجم نافذة ATIM على أداء الشبكة اللاسلكية من ناحية الطاقة المستهلكة ومردود الشبكة اللاسلكية وذلك من خلال عدة سيناريوهات في وضع توفير الطاقة PSM تختلف فيما بينها من ناحية عدد العقد المستخدمة في الشبكة اللاسلكية وحجم نافذة  ATIM.